Perlindungan Hukum dalam Perjanjian Kerja antara Rumah Produksi dan Kru Film pada Produksi Film Televisi - Ari Prasetyowati (Rekam: Jurnal Fotografi, Televisi, Animasi)
This article discusses about the contract between a poduct house and a freelance film worker on a television film production locates in Yogykarta. This article is the result of the research that aims to know about wanprestatie done in a contract. The research is included into an Empiricaljuridical research category. The research is done at Yogyakarta, by selecting the purposive sample. The data used in this research is secondary data of literature references through document study and primary data, which is the data that gained directly by doing interviews. The collected data will be analized qualitatively and will be reported as a descriptive research. The result of this research showed that in dealing with a contract between a production house and freelancer of television film which located in Yogyakarta, may cause wanprestatie possibly happen, such as the fee payment’s pending and inappropriate health supporting. A wanprestatie which might be done by a freelancer is doing resignment before the end term of the contract, a sudden employee’s replacement, and the lateness of a freelancer to go for her/his work, so it causes less profit for a production house. The protection of law for this kind of contract are job contract, working hour, resting hour, salary payment, and technically protection.Keywords: job contract, wanprestatie, law protection